PRIVATISASI BADAN USAHA MILIK NEGARA(BUMN), EKSISTENSI, DAN KINERJA EKONOMI NASIONAL DALAM SISTEM EKONOMI PASAR - Nanang Yusroni; Dumadi Tri Restiyanto (Universitas Wahid Hasyim, 2007)
Privatization of state owner enterprise as an economic politics consequent that must be held by Indonesian Government because the decrease of their performance. But there are many constraints : The enterprise monopolize of public and strategic sector while the other side it has two functions : social and business and both of them has contradictive interests. Many approach has been used for privatization with concern of benefit and impact of this. Keywords :Privatization, social function, business function.